PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI KOLOID DI KELAS XI IPA - Claudia T D Samara; Theresia Wariani; Maria Benedikta Tukan (Jurnal Suluh Pendidikan, 2026)
The Contextual Teaching and Learning (CTL) approach emphasizes the connection between subject matter and students’ real-life contexts to create meaningful learning experiences. This study aims to: (1) describe teachers’ ability to manage chemistry instruction on colloid topics using the CTL approach; (2) analyze students’ learning achievement in terms of knowledge and skills after the implementation of CTL; and (3) describe students’ responses to CTL-based learning. This study employed a quantitative descriptive method with a one-group design (one-shot case study). The population consisted of all eleventh-grade science students at SMA Kristen Maktihan, with a total sampling of 22 students from class XI IPA. Data were collected through observation sheets of teachers’ instructional management, knowledge-based achievement tests, skill observation sheets, and student response questionnaires. Data analysis was conducted descriptively by calculating mean scores and percentages. The results indicate that: (1) the teacher’s ability to manage CTL-based learning on colloid material was categorized as good, with an average score of 4.00; (2) students’ learning outcomes achieved classical completeness, with an average final score of 83.94 (knowledge aspect: 80.45; skills aspect: 89.20), exceeding the school’s Minimum Mastery Criteria (KKM) of 70; and (3) students’ responses to CTL-based learning were highly positive, with an average percentage of 91%. These findings imply that the implementation of the CTL approach is effective in improving the quality of chemistry learning on colloid topics and is recommended for application to other relevant chemistry subject matters.